Digital Marketing Strategy of Threads of Life Ubud in the Context of Local Culture - Perwira, Nanda (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2025)
This study aims to identify and analyze digital marketing strategies based on local culture in creative MSMEs, with a case study focus on Threads of Life in Bali. The background of the research is rooted in the significant role of creative MSMEs in the regional economy, particularly in Bali, which possesses rich cultural heritage as a primary resource. However, in the digital era, business actors face challenges such as limited digital literacy, resource constraints, and the need to preserve cultural authenticity in global marketing. The method used is a Systematic Literature Review (SLR) consisting of planning, literature searches in reputable databases (Scopus, Web of Science, Sinta, Google Scholar), study selection based on inclusion–exclusion criteria, data extraction, and content analysis to identify relevant strategy patterns. The findings reveal that Threads of Life successfully utilizes social media platforms such as Instagram and Facebook, as well as its official website, to develop brand storytelling that emphasizes traditional weaving, sustainability, and community empowerment. The integration of local cultural values such as mutual cooperation (gotong royong) and heritage preservation strengthens brand image and competitiveness in the global market. This study contributes novelty by combining perspectives of digital marketing, cultural preservation, and the creative industry within a single analytical framework. Research recommendations include expanding digital collaborations, developing interactive content, and strengthening sustainability narratives to enhance consumer engagement. These findings are relevant as strategic references for culture-based creative MSMEs seeking to optimize digital marketing without losing their local identity.